The effects of probiotics administration on the gut microbiome in adolescents with anorexia nervosa—A study protocol for a longitudinal, double‐blind, randomized, placebo‐controlled trial. (30th November 2021) - Gröbner, Eva‐Maria; Zeiler, Michael; Fischmeister, Florian Ph. S.; Kollndorfer, Kathrin; Schmelz, Sonja; Schneider, Andrea; Haid‐Stecher, Nina; Sevecke, Kathrin; Wagner, Gudrun; Keller, Lara; Adan, Roger; Danner, Unna; et al.
Abstract: Objective: Knowledge on gut–brain interaction might help to develop new therapies for patients with anorexia nervosa (AN), as severe starvation‐induced changes of the microbiome (MI) do not normalise with weight gain. We examine the effects of probiotics supplementation on the gut MI in patients with AN. Method: This is a study protocol for a two‐centre double‐blind randomized‐controlled trial comparing the clinical efficacy of multistrain probiotic administration in addition to treatment‐as‐usual compared to placebo in 60 patients with AN (13–19 years). Moreover, 60 sex‐ and age‐matched healthy controls are included in order to record development‐related changes. Assessments are conducted at baseline, discharge, 6 and 12 months after baseline. Assessments include measures of body mass index, psychopathology (including eating‐disorder‐related psychopathology, depression and anxiety), neuropsychological measures, serum and stool analyses. We hypothesise that probiotic administration will have positive effects on the gut microbiota and the treatment of AN by improvement of weight gain, gastrointestinal complaints and psychopathology, and reduction of inflammatory processes compared to placebo. Conclusions: If probiotics could help to normalise the MI composition, reduce inflammation and gastrointestinal discomfort and increase body weight, its administration would be a readily applicable additional component of multi‐modal AN treatment. Key points: Patients with anorexia nervosa face profound alterations of the gut microbiome which does not normalise with weight gain. Alterations in the gut microbiome in patients with anorexia nervosa are linked to psychopathological symptoms and neurophysiological deficits, for example, related to the reward system. This is the first study examining the effects of probiotics administration in adolescents with anorexia nervosa using a randomized controlled trial design.